Fatty alchohol and fatty aldehyde dehydrogenases of Yarrowia lipolytica - Matatiele, Puleng Rose (University of the Free State, 2005)
The cytochrome P-450 monooxygenase and b-oxidation systems of alkane-utilizing yeasts have been studied extensively, whereas very little is known about the fatty (long chain) alcohol and fatty aldehyde oxidizing enzymes. With the recent completion of sequencing of the genome of Yarrowia lipolytica, an alkane-degrading yeast, several putative aldehyde dehydrogenases (ALDHs) have been identified. Four of these were identified as fatty ALDHs (FALDHs). Northern blot analysis and RT-PCR showed that one of the FALDH genes, labelled FALDH4, is induced during growth of Y. lipolytica on alkanes, whereas another aldehyde dehydrogenase gene, labelled ALDH1, was constitutively expressed. Functional analysis of the four FALDH isogenes was initiated by single gene deletion of the four fatty aldehyde dehydrogenase isogenes in all possible combinations. The Cre-loxP recyclable tools system was used for gene disruption. Growth properties of the triple and quadruple deletion strains on alkanes were investigated. A slightly arrested growth in hexadecane was observed in two strains, the triple deletion mutant with intact FALDH2 isogene and the quadruple deletion mutant with all four FALDH isogenes deleted. Very strong hydrophobicity during growth of these mutants in hexadecane was also observed. At this stage one can only say that disruption of FALDH isogenes had a slight negative effect on growth of this yeast on alkanes.; However, it is not yet clear which individual isogenes are the most important for alkane metabolism in this organism. Although fatty aldehyde dehydrogenase (FALDH) activity has been detected in fungi no FALDH genes have yet been cloned, sequenced and expressed. Through BLAST searches using the human FALDH sequence as query we have identified 28 FALDH/FALDH-like gene sequences of which nine are from molds and 19 from yeast species. A comparative study of these sequences showed that fungal FALDH sequences may fall into several different subclasses of the ALDH3 family. Unique features of these proteins included presence of several transmembrane domains and in particular relatively long C- and N-termini. Searches of the sequenced Y. lipolytica genome for fatty alcohol oxidase (FAOD) and fatty alcohol dehydrogenase (FADH) encoding genes, which could be involved in the oxidation of fatty alcohols to aldehydes, yielded only one putative FADH encoding gene. However, FADH activity during growth on n-alkanes was very low and Northern-blot analyses showed that this gene was only eakly expressed during growth on hydrocarbon and non-hydrocarbon substrates.
Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2005
Keywords: Yeast fungi; Alcohol dehydrogenase; Enzymes; Fatty alcohol dehydrogenase; Fatty aldehyde dehydrogenase; RT-PCR; Northern blot; Southern blot; Gene disruptions; Cre-loxP; Fungal FALDHs; Alkanes; Yarrowia lipolytica